Chromosomal instability correlates with poor outcome in patients with myelodysplastic syndromes irrespectively of the cytogenetic risk group - Heilig, Christoph E.; Löffler, Harald; Mahlknecht, Ulrich Rudolph; Janssen, Johannes W. G.; Ho, Anthony Dick; Jauch, Anna; Krämer, Alwin (Journal of cellular and molecular medicine, 2010)
Chromosomal instability (CIN), defined by an elevated frequency of the occurrence of novel chromosomal aberrations, is strongly implicated in the generation of aneuploidy, one of the hallmarks of human cancers. As for aneuploidy itself, the role of CIN in the evolution and progression of malignancy is a matter still open to debate. We investigated numerical as well as structural CIN in primary CD34-positive cells by determining the cell-to-cell variability of the chromosome content using fluorescence-in situ-hybridization (FISH). Thereby, CIN was measured in 65 patients with myelodysplastic syndromes (MDS), acute myeloid leukaemia (AML) and control subjects. Among MDS patients, a subgroup with elevated levels of CIN was identified. At a median follow-up of 17.2 months, all patients within this ‘high CIN’ subgroup had died or progressed to AML, while 80% of MDS patients with normal CIN levels had stable disease (P < 0.001). Notably, there was no statistically significant difference between ‘normal CIN’ and ‘high CIN’ MDS patients regarding established risk factors. Hence, elevated CIN levels were associated with poor outcome, and our method provided additional prognostic information beyond conventional cytogenetics. Furthermore, in all three MDS patients for whom serial measurements were available, development of AML was preceded by increasing CIN levels. In conclusion, elevated CIN levels may be valuable as an early indicator of poor prognosis in MDS, hence corroborating the concept of CIN as a driving force in tumour progression.